Metal oxides modified multiwalled carbon nanotubes based biosensor for determination of hypoxanthine - Thole, Dina. (My University, 2022)
Heart and Stroke Foundation South Africa (HSFSA) reports that about 17.3% of deaths in the country are associated with heart-related diseases and this rate is expected to increase to 41% by the year 2030. This severe increase in death cases is related to diseases caused by consumption of meat (i.e., pork, fish, red meat, and poultry) with high levels of hypoxanthine. Therefore, this raises the need to investigate and detect hypoxanthine levels in the meat. This study aimed at developing a highly stable and sensitive biosensor for the detection of hypoxanthine in fish meat using the glassy carbon electrode (GCE) modified with carbon nanocomposites materials (consisting of metal oxides doped multi-walled carbon nanotubes (MO-MWCNTs) that are treated with amine groups) and an enzyme, xanthine oxidase (XOD) as a catalyst. The sol gel method was used to prepare the metal oxides including zinc oxide (ZnO), zirconium dioxide (ZrO2), manganese (MnO2), cobalt oxide (Co3O4), and titanium dioxide (TiO2). The in-situ method of functionalisation of MWCNTs was employed to increase their current outputs/sensitivity using selected amines, namely, methylenediamine, hydrazine, ethylenediamine (EDA), and triethylenetetramine (TETA). The electrochemical properties of the metal oxides and amine functionalised MWCNTs were studied using both cyclic and differential pulse voltammetry. Fourier transform infrared spectroscopy (FTIR) confirmed the presence of carboxyl (COOH), hydroxyl (OH), and amino (NH2) groups on the surface of the modified MWCNTs; as well as formation of stretching vibrations which appear at lower wavelengths due to the metallic species within the nanocomposite. Thermal gravimetric analyser (TGA) was employed to determine the thermal stability of the nanocomposite. Scanning electron microscopy (SEM) was used to confirm the composite structure and correct deposition of the metal oxides on the walls of MWCNTs. XRD was used to confirm correct structure formation, the crystallinity, and the purity of the nanocomposite. Optimum conditions of the developed biosensor were determined, and the application of the developed biosensor was undertaken on fish meat bought at the local supermarket using the Cyclic and Differential pulse voltammetric techniques. Two highly electrochemical metal oxides among others were TiO2 and Co3O4. The modified MWCNTs containing TETA possess good electrochemical properties with improved sensitivity and selectivity towards hypoxanthine. The presence of metal oxides on MWCNTs and their treatments with amines as confirmed by techniques such as TGA, SEM, XRD, and FTIR have provided a suitable matrix for the immobilisation of the enzyme, namely, xanthine oxidase at 0.5 unit (U). TGA results showed that the unmodified MWCNTs decompose at around 600 0C, but when they are modified with acids and amine decomposition starts at 230 0C, proving that functionalisation of MWCNTs tempers with their thermal stability. Based on the SEM morphological results, attachment of the amines and metal oxides on MWCNTs was seen at x60 000 magnification. Morphology of acid treated MWCNTs appeared thinner, revealing that acids tends to deteriorate the MWCNTs, while the amino treated MWCNTs appeared well modified with less damage on the MWCNTs. XRD confirmed the successful purification of MWCNTs with the intense diffraction peak at 260 that can be assigned to the (002) reflection of graphite. The strong diffraction peak at 250o and a broad peak at 450 indicate that the titania nanoparticles are pure and in the anatase phase. They also show successful deposition of the titanium dioxide onto the surface of the MWCNTs. However, on the formation of cobalt oxide two phases were observed which were CoO, and Co3O4, and on bimetallic nanocomposite (cobalt titanium oxide) also two phases were observed which were CoTiO3, and Co2TiO4. It was found that the sensor performs better at 25 oC at a pH of 7.5 in a phosphate buffer at concentration of 5 mM. The limit of detection of the biosensor was found to be 0.16 nM. The highly electroconductive electrode was XOD/3%Co2TiO4-MWCNTs-TETA/GCE, which was selected for analysis of fish meat. The biosensor has shown low interfering values with high stability, good reusability retaining 73.4% of its initial performance after 50 days of continuous study. The excellent results were obtained on fish meat analysis using cyclic and differential pulse voltammetry revealed that even meat which is deep frozen can also deteriorate as time passes by. Altogether, the findings from this study suggest that the developed biosensor is a reliable analytical tool for the determination of freshness of fish meat using hypoxanthine levels as a marker
Thesis (M.Sc. (Chemistry)) -- University of Limpopo, 2022
Keywords: Heart disease; Hypoxanthine; Metal oxide; Metallic oxides; Carbon nanotubes; Heart disease; Lesch-Nyhan syndrome